(untitled) (World Science, 2019)
In addition to diseases, the examination of the gallbladder and extrahepatic biliary tract reveal functional changes (excesses of the gallbladder, stagnation of bile) and individual anatomical features that do not affect the functioning of the system as a whole, do not cause painful sensations, but in unfavorable conditions lead to the development of diseases (formation of gallbladder stones, mechanical obstacles and acute inflammatory processes). In the course of our research, we determined the frequency of occurrence of asymptomatic bile stagnation, depending on the localization of excesses of the gallbladder in adults without pathology of the hepatobiliary system. The protocols of ultrasound examination of adults with pathology of the hepatobiliary system, performed with the ultrasound machine RadmirUltimaPU, were analyzed. In the first age group, combination of gallbladder excess and bile stagnation was found in 7.1% (both men and women) of all surveyed. In the second age group, this indicator was 50% for men and 35.7% for women. Excesses of the gallbladder is more common in males - 21.6%, in women - 15%. Their frequency increases with age. The timely detection of functional features of the gallbladder in combination with the application of preventive recommendations can prevent the development of the disease.